Peran Manajemen Kearsipan Dalam Pengelolaan Tata Persuratan - Simangunsong, Arimbi Syahkila; Salamah, Imas Ayu; Situmorang, Mela Safitri; Azrohid, Fauzan; Darmansah, Tengku (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Archives management is very important and is a necessity to continue to progress in its services, proper and accurate control of archives, apart from being an asset for an agency, is also useful as material for organizational decision making, because with archives or files that are prepared and accurate, choice making can be achieved. , carried out quickly and accurately. The method in this article uses library research, namely a method of collecting data by understanding and studying theories from various literature related to the research. The conclusions are; By using good records management, organizations can increase efficiency and effectiveness in managing correspondence. Archives management also helps organizations save costs, improve service quality, and increase document security.